Sejarah dan Jejak Peradaban Islam di Andalusia - Inaya Fallina Revanti; Amanda Ayu Amelia; Wahyu Mahfud Hidayat (Jambura History and Culture Journal, 2026)
Andalusia is a symbol of the glory of Islamic civilization and became one of the most advanced centers of Islamic civilization in the world, especially during the Umayyad Caliphate in Cordoba. The objectives of this study are 1) to understand the history of Islamic civilization in Andalusia; and 2) to identify traces of Islam in Andalusia that can still be seen today. This article uses a qualitative approach with a historical method consisting of stages including source collection, verification, interpretation, and historiography. The results of the writing show that the history of Andalusia is not only Spain or the Islamic world, but a shared heritage of humanity that teaches the importance of tolerance and steadfastness in facing ever-changing times. Although Islamic rule in Andalusia has ended, the values and contributions left behind remain alive and become the basis for the development of modern civilization, especially in encouraging the advancement of science and culture in Europe.